Molecular foundations of chiropractic therapy - Maltese, Paolo Enrico; Michelini, Sandro; Baronio, Manuela; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Alternative medicine is a broad term used to encompass different therapies, including chiropractic. Chiropractic was called “a science of healing without drugs” by its founder, David Daniel Palmer. It is based on the idea that the body has a powerful self-healing ability and that there is a relationship between body structure and function that affects health. In particular, chiropractic assumes that the nervous system controls the human body through nerves branching from the vertebral column and spinal cord. Researchers do not fully understand how chiropractic therapies affect pain, but chiropractic is widely used today to treat chronic pain, such as back pain. Different studies with animal models have demonstrated that chiropractic therapies mediate neuroplasticity, specifically through modulation of neurotrophins. No studies have yet been published on interaction between neurotrophin gene polymorphisms and chiropractic treatment. Methods: We searched PubMed with the following keywords: chiropractic, neuroplasticity, neurotrophin gene polymorphism for a panorama of on the molecular mechanisms of chiropractic therapy. Results: From the material collected, we identified a set of genes and some functional polymorphisms that could be correlated with better response to chiropractic therapy. Conclusions: Further association studies will be necessary to confirm hypotheses of a correlation between single nucleotide polymorphisms in specific genes and better response to chiropractic therapy.